2020
DOI: 10.1371/journal.pone.0232620
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of HIV testing among Filipino women: Results from the 2013 Philippine National Demographic and Health Survey

Abstract: Background The prevalence of having ever tested for HIV in the Philippines is very low and is far from the 90% target of the Philippine Department of Health (DOH) and UNAIDS, thus the need to identify the factors associated with ever testing for HIV among Filipino women. Methods We analysed the 2013 Philippine National Demographic and Health Survey (NDHS). The NDHS is a nationally representative survey which utilized a two-stage stratified design to sample Filipino women aged 15-49. We considered the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…The factors that were eventually found to be associated with HIV testing (e.g., education, socio-economic status, etc.) were similar with the results to a previous study (21). Furthermore, the lack of association between being a victim of IPV and HIV testing has been previously documented in literature.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The factors that were eventually found to be associated with HIV testing (e.g., education, socio-economic status, etc.) were similar with the results to a previous study (21). Furthermore, the lack of association between being a victim of IPV and HIV testing has been previously documented in literature.…”
Section: Discussionsupporting
confidence: 92%
“…From these cross-tabulations, we control for the effect of the following confounders in the regression model: alcohol intake of partner, educational attainment of respondent, educational attainment of partner, domicile, religion, newspaper, weekly access to radio, tv and internet, wealth index, employment status, marital status, tobacco use, alcohol consumption, age of respondent, household size, age of partner, number of lifetime sexual partners, and tolerance to domestic violence score. Even if women's empowerment score, having a father who beats her mother, and controlling behavior of partner is not associated with our outcome from the data, we will still be controlling for these variables because previous studies have shown that these are known to confound the main association of interest (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). We also assessed the potential confounding effect of the other remaining variables through regression modelling, but we did not nd any, hence they were not controlled for in our nal models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV is a significant health disparity affecting those living in the Philippines and prevalence is increasing at an alarming rate. The fact that these rates are increasing so quickly with such low testing rates (< 3%) suggests that more people are suffering from HIV and education and testing programs are needed to reduce the burden of disease [12,13,18]. One method of addressing marked public health issues is to improve awareness.…”
Section: Limitationsmentioning
confidence: 99%